Komposisi Spesies dan Struktur Komunitas Ikan di Kawasan Ekosistem Mangrove Muara Sungai Musi Kabupaten Banyasin Sumatera Selatan - Juaini Anggraini; Fitri Agustriani; Isnaini Isnaini (Jurnal Penelitian Sains, 2019)
The mangrove forests is the most important area that must be maintained. Mangrove forests can be covered by vegetation such as Avicennia , palm, and the other that has fundamental in preserving the fishery resources. Fishery resources are classified as a renewable but limited by natural factors and non-natural factors. This study was aimed to analyze species composition, community structure and fish size composition and measure estuary parameters at Musi river. This study was conducted on December 2015 at the estury of Musi river ini Banyuasin, South Sumatera. Survey method was used in this study by measuring the length and weight of the fish cathced by drift gill net. The results of this study found 24 species of fish. Overall community structure at station 2-5 and has a lower category because no one dominates, whereas at station 1 had a high dominance of 0.82 but with the amount of catches was only 2 types by the number of species is not too many. The length and weight of Eleutheronema tetradactylum: 23.9-28.6 cm (26%), 103.5-202.4 g (34%), Engraulis grayi: 11.4-13.1 cm (15%), 6- 22.7 g (37%), Pseudocienna amovensis: 17.9-19.5 cm (24%), 60.1-75.7 g (24%), Setipinna melanochir: 20.8-21.6 (17%,), 58.4-68.7 g (17%). Water quality parameters for temperature, pH, salinity and water stream at the estuary of Musi river were categorized in good condition for aquatic biota.